Characterization of palm oil fuel ash (POFA) and fly ash blend in geopolymerization process - Nor Saiyidah, Abd Ghani (2013)
Malaysia as the world largest exporter of palm oil was succeeded continuously increasing the production of palm oil but has been facing problems in disposing palm oil fuel ash (POFA),. a by-product of palm oil mill. Since the manufacturing process of Portland cement produced greenhouse gases, previous researchers were revealing the potential of this by-product as the partial cement replacement and reacted as pozzolans in concrete paste. Therefore, Geopolymer is proposed in this study since it nullifies the usage of ordinary Portland cement (OPC) in concrete -while maintaining the consumption of by-product through its usage as the source material in geopolymer. The effectiveness of fly ash-POFA based geopolymer was developed as an alternative material to replace usage of OPC. POFA were used to replace fly ash in geopolymer by 0%, 12.5% and 25% by weight of fly ash. The compressive strength of fly ash-POFA based geopolymer concrete paste due to 1, 7 and 28 days of curing age days with different curing condition were determined. The porosity percentage of fly ash-POFA geopolymer concrete paste due to 1, 7 and 28 days also were tested. In addition, the energy dispersive x-ray (EDX) was conducted in order to determine the basic elemental characteristic of fly ash-POFA based geopolymer binder. It was found that the compressive strength of fly ash-POFA based geopolymer concrete paste was lower than fly ash based geopolymer concrete paste. It also revealed that the compressive strength of concrete paste was increasing due to curing day ages for ambient curing while for oven curing the compressive strength were decreasing. Based on the EDX analysis, the geopolymer formation in fly ash-POFA geopolymer based concrete paste are poly(silate-disiloxo) and sialate link.